Analisis Kesalahan dalam Menyelesaikan Soal Bentuk Aljabar Ditinjau dari Taksonomi SOLO - Kunim Sriati; Sudi Prayitno; Nurul Hikmah; Laila Hayati (Griya Journal of Mathematics Education and Application, 2021)
The aim of this study is to describe the types of errors and their causes made by the seven grade students of SMPN 7 PUJUT in the academic year 2020/2021 in solving algebraic form questions based on the SOLO taxonomy level. This research is a qualitative descriptive study and the instruments used are test questions and interview guides. The subjects of this study were 32 grade seven students of SMPN 7 PUJUT who were selected using purposive sampling technique. After selecting one class, several students were selected according to the SOLO taxonomy level. The results showed that all students made the types of errors according to the basic objects of mathematics, namely fact errors, concept errors, operating errors, and principle errors. The results also showed that the questions given to 32 class seven students of SMPN 7 PUJUT obtained a percentage of the structural level of 31.25%, the unistructural level of 37.5%, the multistructural level of 21.9%, the relational level of 9.38%, and the extended abstract level is 0%. The causes of students making mistakes in solving questions, namely: the cause of factual errors is that students do not understand the meaning of the questions which include what is known and asked and in determining the final result; the cause of misconceptions is that students do not understand the formula used; the cause of the operation error is that the students are not careful in calculating; and the cause of the principle error is that students do not understand the steps to solve it.